Can there be overly meaningful lives? Conflicts between meaning in life and other values - Landau, Iddo (Frontiers in Psychology, 2022)
This is a philosophical paper that heeds psychological work on meaning in life, and hopes to acquaint both psychologists and philosophers more with each other’s work and enhance a dialogue between them. Many works on meaning in life in philosophy and in psychology have already focused on the relations between meaning in life and specific values such as happiness (subjective wellbeing), authenticity, morality, knowledge, and artistic creation. This paper discusses the general structure of the relation between both objective and subjective meaning in life and other values, and emphasizes ways in which such values sometimes conflict with rather than enhance objective or subjective meaning in life. The paper argues that, because of such conflicts, there are cases in which we should refrain from augmenting the objective or subjective meaning in our lives and even seek to decrease it; there can be overly meaningful lives. The paper concludes with some practical implications of this discussion.